2015
DOI: 10.1016/j.anorl.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Cervicofacial cellulitis: The impact of non-steroidal anti-inflammatory drugs. A study of 70 cases

Abstract: CFC is a severe infection that can be life-threatening, and represents a diagnostic and therapeutic emergency. Among other risk factors, use of NSAIDs is frequently reported; these should therefore be used with caution if at all in head and neck infection, especially of odonto-stomatological origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 20 publications
1
15
0
8
Order By: Relevance
“…Because this mechanism of action is distinct from that of opioids, NSAIDs have the potential to produce adequate levels of pain relief while reducing overall opioid requirements and associated AEs [ 17 ]. However, NSAIDs are associated with their own potential AEs, including gastropathy, renal impairment, potential to prolong bleeding via platelet inhibition [ 16 ], and possible increased risk of severe infection [ 18 ] or acceleration of an infectious disease course [ 19 ]. As such, it is important to characterize the evidence for benefits and risks associated with NSAID use in order to determine their clinical utility as part of the pain management strategy for pediatric patients.…”
Section: Introductionmentioning
confidence: 99%
“…Because this mechanism of action is distinct from that of opioids, NSAIDs have the potential to produce adequate levels of pain relief while reducing overall opioid requirements and associated AEs [ 17 ]. However, NSAIDs are associated with their own potential AEs, including gastropathy, renal impairment, potential to prolong bleeding via platelet inhibition [ 16 ], and possible increased risk of severe infection [ 18 ] or acceleration of an infectious disease course [ 19 ]. As such, it is important to characterize the evidence for benefits and risks associated with NSAID use in order to determine their clinical utility as part of the pain management strategy for pediatric patients.…”
Section: Introductionmentioning
confidence: 99%
“…From an epidemiological point of view, the 2007 study by Rakotoarison et al [10] showed an increase in the number of cases of cervicofacial cellulitis due to the misuse of drugs, especially in cases of self-medication with uncontrolled antiinflammatory drugs and antibiotics. Nonsteroidal anti-inflammatory drug abuse is found in more than half of the cases (up to 80%) according to the study by Bennani-Baïta et al [11]. Among the subjects most affected by diffuse cellulitis are men aged between 20 and 30 years, patients with poor oral hygiene, and those belonging to poor socioeconomic classes.…”
Section: Discussionmentioning
confidence: 99%
“…Local homecare for tracheostomy opening and cervicotomy scar was provided by a nurse, and regular clinical checks in the maxillofacial surgery department were performed, with a favorable prognosis. Consultation with a dental surgeon was necessary for general prosthetic rehabilitation with the extraction of the remaining non-conservable teeth (11,12, and 23) and making of complete maxillary and mandibular removable prostheses.…”
Section: Casementioning
confidence: 99%
“…If the infection is of sinus origin, this group is the most frequently found (18%), followed by staphylococci (17%) and Gram-negative bacteria (15%). Taking NSAIDs is a likely risk factor, or at least an aggravating factor, even though no studies could scientifically prove it [6]. NSAIDs alleviate symptoms and delay diagnosis.…”
Section: Discussionmentioning
confidence: 99%